Liderazgo estratégico y su influencia en la competitividad de la Empresa de Productos Lácteos El Ranchito. - Viera Espinel, Roosevelt Fabián (2023)
This research work focused on establishing the correlation between strategic leadership and its influence on competitiveness for the El Ranchito Dairy Products Company. The study population by census sampling was 35 employees and workers. The research used the deterministic construct technique with 30 questions generated through a data order classifier to establish the degree of differentiation between the analyzed variables. The information was applied and processed in Excel and SPSS 27 where we quantified the level of confidence of the variables through expert judgment, the validity of the content was developed through AIKEN's Technique V and corroborated with CRONBACH's ALFA; Furthermore, based on SPEARMAN's RHO test, we determined the relationship between the two variables involved in this study; Finally, by inferring the results obtained, it was possible to conclude the relational non-existence between strategic leadership and competitiveness in the El Ranchito Dairy Products Company, as a result, the hypothesis put out in this study is accepted, as there would be an incremental relationship between strategic leadership and competitiveness with a very significant positive correlation.